Balloon kyphoplasty as palliative care for painful pathological spinal fracture followed by lung cancer metastasis: A cohort study - Zhang, Jun-xin; Song, Zhuo-run; Zou, Jun; Ge, Jun; Yang, Hui-lin (Frontiers in Surgery, 2023)
Purpose: Pathological spine fractures caused by metastases of lung cancer have brought great suffer to patients. Percutaneous kyphoplasty (PKP) has been considered as a preferred alternative for painful spinal metastases. The clinical efficacy and safety of PKP for metastatic spinal lesions are urgent to be evaluated. Methods: A cohort study was conducted on 54 cases with pathologic spine fractures caused by metastasis of lung cancer. The correction of kyphosis was assessed by Cobb angle. The life dependence and quality of the patients were evaluated by Barthel Index of ADL and Quality-adjusted Life Year (QALY). Patients’ survival was carefully recorded. Results: PKP significantly corrected the kyphosis compared to conservative treatment. The ratio of moderate dependence after fracture was clearly increased by PKP. QALY indicated a better life quality brought by PKP. However, PKP could not improve the survival rate of patients. Conclusion: PKP can be used as an effective palliative care for patients with metastatic pathologic spinal fractures of lung cancer.